2012
DOI: 10.1007/s10072-012-1261-0
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and epilepsy in elderly patients of an urban area of Iran: clinical manifestation, differential diagnosis, etiology, and epilepsy subtypes

Abstract: The incidences of seizures and epilepsy in the population show a peak after 60 years of age. Due to the lack of reported clinical aspects of seizure and epilepsy in the older patients in our region in Iran, this study was conducted to describe the clinical manifestation, etiology, differential diagnosis, and epilepsy subtypes of epilepsy and seizure. A cross-sectional retrospective study was performed on all consecutively elderly seizure and epilepsy patients, referred to the Epilepsy Association in the city o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
3
12
1
3
Order By: Relevance
“…Some studies have, however, reported that 75% of older people with epilepsy had generalized seizures [10] while another study found no differences [11]. It is likely that the high occurrence of cerebral pathology in older people is responsible for the predominance of focal-onset epilepsy in our group.…”
Section: Seizure Semiologymentioning
confidence: 91%
“…Some studies have, however, reported that 75% of older people with epilepsy had generalized seizures [10] while another study found no differences [11]. It is likely that the high occurrence of cerebral pathology in older people is responsible for the predominance of focal-onset epilepsy in our group.…”
Section: Seizure Semiologymentioning
confidence: 91%
“…In other similar studies, patients' average age was not specified or the subjects were within a limited age range. For instance, Tabatabaei et al performed a study on patients above 60 years over ten years (15).…”
Section: Discussionmentioning
confidence: 99%
“…The most common differential diagnoses were syncope and cardiovascular disorders. In addition, 27% and 24% had systemic metabolic disorders and cerebrovascular diseases, respectively (15).…”
Section: Discussionmentioning
confidence: 99%
“…İran'da 2013'te yapılan bir çalışmada da jeneralize nöbet oranları %75 gibi yüksek bulunmuştur. [3] Hasta grubumuzda nöbetlerin 21 tanesi atipik bulgularla presente idi ve sıkı takip sonucu ve EEG bulguları yardımıyla kesin tanıya ulaşıldı.…”
Section: Kaynaklarunclassified
“…[1,2] Yaşlı hastalarda epilepsiler etiyolojik faktörler açısından da genç hastalardan daha farklıdır ve yaşlılarda eşlik eden hastalıklar nedeniyle farmakolojik etkileşimler de önemlidir. [3,4] Bu çalışmada, kliniğimiz epilepsi polikliniğinde takip edilen epilepsi hastaları içinde yaşları 65 üzerinde olanlar çalışma-ya alındı ve nöbet tipi, etiyoloji, tedavi ve prognoz açısından incelendi.…”
Section: Introductionunclassified